Application of Monoterpenoids and their Derivatives for Treatment of Neurodegenerative Disorders - Volcho, Konstantin P; Laev, Sergey S; Ashraf, Ghulam Md; Aliev, Gjumrakch; Salakhutdinov, Nariman F (Current medicinal chemistry, 2018)
Neurodegenerative disorders (NDDs) like Alzheimer's disease, Parkinson's disease and Huntington's disease are a heterogeneous group of disorders with the progressive and severe loss of neurons. There are no full proof cures for these diseases, and only medicines are available that can alleviate some of the symptoms. Developing effective treatments for the NDDs is a difficult but necessary task. Hence, the investigation of monoterpenoids which modulate targets applicable to many NDDs is highly relevant. Many monoterpenoids have demonstrated promising neuroprotective activity mediated by various systems. It can form the basis for elaboration of agents which will be useful both for the alleviation of symptoms of NDDs and for the treatment of diseases progression and also for prevention of neurodegeneration. The further developments including detections of monoterpenoids and their derivatives with high neuroprotective or neurotrophic activity as well as the results of qualified clinical trials are needed to draw solid conclusions regarding the efficacy of these agents.